Clinical and radiographical evaluation of pulpotomy in primary molars treated with Pulpotec (PD), Formocresol and Mineral Trioxide Aggregate (MTA) - Zeyneb A A Al- Dahan; Abeer M Zwain; Aseel Haidar H M Al-Assadi (College of Dentistry/ University of Baghdad, 2013)
Background: Pulpotomy is an accepted treatment for the management of cariously exposed pulps in symptom free primary molars to achieve one of the most important goals for Pedodontists, which is the retention of the pulpally involved deciduous teeth healthy until the time of normal exfoliation. The purpose of this study was to evaluate the relative success of pulpotec, formocresol and Mineral Trioxide Aggregate (MTA) in cariously exposed primary molar teeth, using clinical and radiographical examinations. Materials and methods: Thirty nine children with 45 primary molars requiring pulpotomy were selected in this study, 15 teeth treated by each type of pulpotomy medicament. Clinical and radiographical follow up for the patients was performed after 1 month, 3 months and 6 months respectively. Results: After six months, the clinical success rate of the Pulpotec group was (93.3%), formocresol group was (73.3%) and (100%) for the MTA group, although the success rate of the formocresol group was the least comparing to the other two groups, it was statistically not significant (P= 0.05). The highest and lowest radio graphical success rates after six months, were encountered in the MTA (100%) and formocresol (66.7%) groups respectively, which showed a significant difference (P=0.04). The radiographical success rate of the pulpotec group was (86.7%). Conclusion: This study suggests that Pulpotec and MTA can be used as a replacement for formocresol as a pulpotomy medicament in primary molar teeth.